A study on users’ satisfaction on lighting in libraries / Muhammad Mustaqim Sapri and Neta Suredah Baharum - Sapri, Muhammad Mustaqim; Baharum, Neta Suredah (2018)
Library provides spaces for user to study for both concentration and relaxation. In addition to proper ambience and shelf lighting, the atmosphere needs to be welcoming. Lighting gives major influences on users' satisfaction and visual comfort in libraries. This study is based on the influence of artificial lighting in library on users’ productivity and performance especially user satisfaction based on the lighting guidelines by the local authorities. Several methods were used to gather information and data which include the scale and location of study, physical measurement, questionnaire survey and cross tabulation of data. The results that come from this study can be used to improve artificial lighting in library by enhancing studying environment thus motivating users to stay longer.